Subacute Demyelinating Polyneuropathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The electroclinical characteristics of 5 children (ages 4-13 years) with subacute inflammatory demyelinating polyneuropathy (SIDP) are reported from the Royal Children's Hospital, Victoria, Australia.